Numerical analysis of forming the tri-layer non-homogeneous bellows via the hydroforming process - Pezhman Ghanbari; Behnam Akhoundi; Vahid Modanloo (Trends in Computer Science and Information Technology - Peertechz Publications, 2023)
Due to the complex and structural characteristics of non-homogeneous layers in hydroforming, their forming is a challenging process. In this research, the manufacturing process of three-layered bellows made of 304 stainless steel (two outer layers) and Inconel 718 (inner layer) is numerically investigated. The effects of different parameters on the forming of bellows are studied. To study the effect of friction between layers, two models are used; a model with friction between layers and a model with tied layers. It is observed that the amount of displacement in the model with a tie connection is more. The maximum values of stresses are detected in the inner region after the second stage of forming, i.e. folding. These values reduce after the spring-back step.